Low-Dose Pegylated Interferon-α2A plus Ribavirin Therapy for Elderly And/Or Cirrhotic Patients with HCV Genotype-1B and High Viral Load. Issue 1 (January 2014) - Tamai, Hideyuki; Mori, Yoshiyuki; Shingaki, Naoki; Kawashima, Akira; Tsukuda, Hiroshi; Higashi, Katsuhiko; Moribata, Kosaku; Kawaguchi, Masanori; Ueda, Kazuki; Deguchi, Hisanobu; Inoue, Izumi; Maekita, Takao; et al.
Background: Pegylated interferon (PEG-IFN) plus ribavirin therapy is still recommended for elderly and/or cirrhotic patients. This study examined whether sustained virological response (SVR) to low-dose PEG-IFN-α2a plus ribavirin therapy for elderly and/or cirrhotic patients could be predicted based on viral reduction within 2 weeks after therapy initiation or interleukin IL-(28B) polymorphism and viral mutations. Methods: Participants comprised 115 elderly (≥65 years) and/or cirrhotic patients with genotype-1b and high viral load. Reduced doses of PEG-IFN-α2a (90 μg/kg/week) and ribavirin (400-800 mg/day) were administered for 48-72 weeks based on virological response of each patient. Results: SVR was achieved in 34% (39/115), and treatment was discontinued in 15% (17/115). Univariate analysis identified age, α-fetoprotein, fibrosis marker, interferon sensitivity-determining region (ISDR), IL-28B polymorphism and level of viral reduction within 2 weeks as factors contributing significantly to SVR. However, no significant differences were noted in core amino acid substitutions. Multivariate analysis identified age, hyaluronic acid, ISDR and viral reduction as factors independently associated with SVR. Positive predictive value (PPV) and negative predictive value (NPV) of SVR based on the level of viral reduction at 2 weeks (cutoff level, 1.7 log IU/ml) were 83% and 84%, respectively. The PPV of SVR based on IL-28B major and ISDR mutant was 70%, and the NPV of SVR based on IL-28B minor and wild-type ISDR was 89%. Conclusions: Evaluations of viral reduction at 2 weeks or both IL-28B and ISDR are useful to predict SVR to low-dose PEG-IFN-α2a plus ribavirin therapy for elderly and/ or cirrhotic patients.